Energy saving strategies in sustainable greenhouse cultivation in the mediterranean climate – A case study. (15th January 2021) - Ouazzani Chahidi, Laila; Fossa, Marco; Priarone, Antonella; Mechaqrane, Abdellah
Highlights: A greenhouse dynamic model is developed by considering all interactive components, including soil, plants and internal masses. The hourly real measurements are compared to the model predictions. The controlled shading/reflecting system and the operable windows can save about 5% and 14% of the energy needs, respectively. The ground coupled heat pump saves around 21% of the primary energy consumption of a traditional air-conditioning system. The semitransparent PV modules provide about 16% of the greenhouse energy demand, throughout the year. Abstract: Greenhouse cultivation is one of the most effective and widely used methods which provide a suitable environment for plants growth. The persisting demand for energy in greenhouses represents the main constraint for this cultivation method. Integrating passive technologies and renewable energies can significantly contribute to reducing the energy consumption. This study presents an EnergyPlus dynamic model of a high-efficiency greenhouse, the "Smart Agro-Manufacturing Laboratory" (SamLab), located in Albenga, Italy. The SamLab includes different energy-saving integrated systems: a shading/reflecting system for glazed surfaces, operable windows for natural ventilation, a roof with semitransparent PV modules, and a HVAC system with a ground-coupled heat pump. The EnergyPlus model of the greenhouse considers all interactive components in the energy balance, including the plants, the soil and the internal masses, and comparison are performed to assess the influence of each factor. Moreover, the positive effect of the renewable energies is estimated by comparing the primary energy need associated to the actual innovative plant of the greenhouse (PV modules and ground coupled heat pump) with the energy ideally requested by a traditional plant to satisfy the same request of heating and cooling. The results show that the passive technologies can provide a reduction of nearly 16% of the energy needs, during cooling period. Moreover, the ground coupled heat pump saves around 21% compared to a traditional air conditioning system. The PV energy production have been both measured and predicted with good accuracy; this provides around 44% of the yearly electricity needs for air conditioning needs.